Wielding the ax : state forestry and social conflict in Tanzania, 1820-2000 - Sunseri, Thaddeus Raymond (Ohio University Press series in ecology and history., 2009)
Forests have been at the fault lines of contact between African peasant communities in the Tanzanian coastal hinterland and outsiders for almost two centuries. In recent decades, a global call for biodiversity preservation has been the main challenge to Tanzanians and their forests. Thaddeus Sunseri uses the lens of forest history to explore some of the most profound transformations in Tanzania from the nineteenth century to the present. He explores anticolonial rebellions, the world wars, the depression, the Cold War, oil shocks, and nationalism through their intersections with and impacts.